2019
DOI: 10.1007/s11136-019-02384-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German HeartQoL: a short health-related quality of life questionnaire for cardiac patients

Abstract: Purpose The aim of this study was to evaluate psychometric properties of the core disease-specific 14-item German HeartQoL questionnaire. Methods As an extension of the international HeartQol Project, cross-sectional and longitudinal health-related quality of life (HRQL) data were collected from 305 patients with angina (N = 101), myocardial infarction (N = 123), or ischemic heart failure (N = 81) in Austria and Switzerland using German versions of the HeartQoL, the Short Form-36 Health Survey (SF-36), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 30 publications
(50 reference statements)
6
15
0
Order By: Relevance
“…Of the total of 84 discriminative validity calculations in the total cohort and each diagnosis, 70 (83%) were fully confirmed; of the 14 calculations that were not significant, 11 (79%) were on the age and 3 (21%) on the sex variables. The discriminative validity of the Italian HeartQoL was fully confirmed for diagnosis as patients with MI reported significantly higher HeartQoL scores than patients with either AP or IHF which is largely consistent with both the original validation study [13] and the German validation study [14] as well as in the English HeartQoL where patients with MI reported higher HRQL scores than did patients with AP. [30] Discriminative validity was also fully confirmed with HADS anxiety/depression scales in the total group and in each diagnosis which is consistent for HADS anxiety and depression in the original study [13] and previously published HeartQoL studies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Of the total of 84 discriminative validity calculations in the total cohort and each diagnosis, 70 (83%) were fully confirmed; of the 14 calculations that were not significant, 11 (79%) were on the age and 3 (21%) on the sex variables. The discriminative validity of the Italian HeartQoL was fully confirmed for diagnosis as patients with MI reported significantly higher HeartQoL scores than patients with either AP or IHF which is largely consistent with both the original validation study [13] and the German validation study [14] as well as in the English HeartQoL where patients with MI reported higher HRQL scores than did patients with AP. [30] Discriminative validity was also fully confirmed with HADS anxiety/depression scales in the total group and in each diagnosis which is consistent for HADS anxiety and depression in the original study [13] and previously published HeartQoL studies.…”
Section: Discussionsupporting
confidence: 78%
“…The result was a bifactorial, 14-item questionnaire that was reliable, valid, and responsive in patients with AP, MI, or IHF [13]. These results have been recently confirmed in German [14] and Chinese [15] and also in other clinical contexts, such as atrial fibrillation [16], implantable cardioverter defibrillator recipients [17], and valve surgery [18].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In as early as 2004, researchers investigated the psychometric properties of the Hospital Anxiety and Depression Scale (HADS) as a screening instrument for patients with ACS and confirmed that the HADS was useful in assessing symptoms of psychological distress in patients with ACS (Martin et al, 2004 ). Psychometric properties of assorted instruments have been studied in cardiac patients using the Depression in the Medically Ill-18 (DMI-18), the Depression in the Medically Ill-10 (DMI-10), the MacNew Heart Disease HRQL questionnaire (MacNew), the German HeartQoL questionnaire, and the Patient Health Questionnaire (PHQ-9) (Hilton et al, 2006 ; Yu et al, 2008 ; Gholizadeh et al, 2019 ; Huber et al, 2020 ). It can be inferred that the psychometric properties of more instruments will be tested on patients with CHD to determine their validity and reliability of assessing depression and anxiety in a specific group of patients.…”
Section: Resultsmentioning
confidence: 99%
“…MSA is especially suitable for constructing quality of life (related) measures, as the NIRT properties are often sufficient for the intended use of the scales [ 12 ]. Recent examples of quality of life questionnaires that have been analyzed using MSA include the Heart disease-specific health-related quality of life (HeartQoL; [ 13 ]), the Participation and Activity Inventory for Children and Youth (PAI-CY; [ 14 ]), and the Rotterdam Diabetic Foot Study Test Battery (RDF [ 15 ]). In these studies, the data were collected using a simple random sample, yielding nonclustered test scores.…”
Section: Introductionmentioning
confidence: 99%